2017
DOI: 10.1007/s15010-017-1054-8
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of multidrug-resistant tuberculosis in Zambia: a cohort analysis

Abstract: More than half of the patients diagnosed with MDR-TB were lost to follow-up before second-line treatment was initiated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…reported in similar patient cohorts from South Africa [18,19] and Zambia [20], where the majority of patients were co-infected with HIV. However, the better treatment outcomes in the current study may be due to potential selection bias of excluding patients treated at primary health centres.…”
Section: Plos Onementioning
confidence: 58%
“…reported in similar patient cohorts from South Africa [18,19] and Zambia [20], where the majority of patients were co-infected with HIV. However, the better treatment outcomes in the current study may be due to potential selection bias of excluding patients treated at primary health centres.…”
Section: Plos Onementioning
confidence: 58%
“…The current study included only three patients with HIV/AIDS (Table 3). However, we are aware that HIV/AIDS contributes to poor treatment outcomes [3,13,54], and that patients taking ART have a lower risk of dying [5]. Girum et al found that HIV/AIDS positive patients with MDR-TB were three times more liable to die compared with seronegative patients [61].…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) believes over 10 million people globally fell ill with tuberculosis (TB) in 2017 and 2018, although the number actually reported is only 7 million [1,2]. Drug-resistant TB continues to be a global public health concern with approximately 580,000 cases worldwide and mortality worse than most cancers [1,[3][4][5][6]. Overall, TB is the leading cause of death among patients with infectious diseases [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Both Rifampin (RIF) and Isoniazid (INH) resistance are reliable markers of MDR-TB [9]. Drug-resistant TB remainsto be a universalpublic health concern, with nearly580,000 cases worldwide and mortality rates higher than most cancers [1,[10][11][12][13]]. WHO's surveillance data estimated 600000MDR-TBcasesand deaths of 490000 people with MDR-TB in 2016 [3].…”
Section: Introductionmentioning
confidence: 99%